The Linked Dual Representation model of vocal perception and production - Hutchins, Sean; Moreno, Sylvain (Frontiers in Psychology, 2013)
The voice is one of the most important media for communication, yet there is a wide range of abilities in both the perception and production of the voice. In this article, we review this range of abilities, focusing on pitch accuracy as a particularly informative case, and look at the factors underlying these abilities. Several classes of models have been posited describing the relationship between vocal perception and production, and we review the evidence for and against each class of model. We look at how the voice is different from other musical instruments and review evidence about both the association and the dissociation between vocal perception and production abilities. Finally, we introduce the Linked Dual Representation model, a new approach which can account for the broad patterns in prior findings, including trends in the data which might seem to be countervailing. We discuss how this model interacts with higher-order cognition and examine its predictions about several aspects of vocal perception and production.